Mathematical modeling and physical reality in noncovalent interactions - Politzer, Peter; Murray, Jane S.; Clark, Timothy (Journal of Molecular Modeling, 2015)
The Hellmann-Feynman theorem provides a straightforward interpretation of noncovalent bonding in terms of Coulombic interactions, which encompass polarization (and accordingly include dispersion). Exchange, Pauli repulsion, orbitals, etc., are part of the mathematics of obtaining the system's wave function and subsequently its electronic density. They do not correspond to physical forces. Charge transfer, in the context of noncovalent interactions, is equivalent to polarization. The key point is that mathematical models must not be confused with physical reality.
Keywords: Noncovalent interactions; Hellmann-Feynman theorem; Electrostatic potential; Polarization; Charge transfer; Dispersion; sigma-hole interactions; Halogen bonding; Hydrogen bonding